Given: The system of equations below
![\begin{gathered} equation1:6x-5y=3 \\ equation2:3x-8y=-15 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/170d1f98e2rsv4t0tdq0bht8r4gboaqdlr.png)
To Determine: The solution of the equations
Solution
Step 1: Eliminate x by multiplying equation 1 by 1 and equation 2 by 2
![\begin{gathered} 1*(6x-5y=3)\rightarrow6x-5y=3 \\ 2*(3x-8y=-15)\rightarrow6x-16y=-30 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/68ytor2iapo24te4gkyn2ied4vcz6y9tl2.png)
Step 2: Subtract derived equation from equation 2 from the derived equation from equation 1
![\begin{gathered} (6x-5y=3)-(6x-16y=-30) \\ 6x-6x-5y--16y=3--30 \\ -5y+16y=3+30 \\ 11y=33 \\ y=(33)/(11) \\ y=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3hr3owxy200od6ye6b0yux5zflw3zcy3jw.png)
Step 3: Substitute the value of y into equation 1
![\begin{gathered} 6x-5y=3 \\ 6x-5(3)=3 \\ 6x-15=3 \\ 6x=3+15 \\ 6x=18 \\ x=(18)/(6) \\ x=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/d8arygyidzfy5wltizhkw99i1uruzr4sce.png)
Hence, x = 3, y = 3
(3,3)